Method for preparing recycled aggregate concrete with high fatigue load resistance and recycling aggregate

By adding magnesium-aluminum hydrotalcite, fly ash and silica fume to the recycled concrete and using a specific process treatment, the recycled aggregate concrete exhibits high compressive and flexural strength under fatigue loads, solving the problem of poor fatigue performance of existing recycled aggregate concrete and achieving efficient reuse of aggregates.

CN119707393APending Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411866763.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing recycled aggregate concrete exhibits high variability and reduced fatigue strength under fatigue loads, resulting in the problem of reliability and service life in engineering applications.

Method used

Recycled concrete with high fatigue load resistance is formed by adding magnesium-aluminum hydrotalcite, fly ash and silica fume to the recycled concrete and adopting a specific stirring and curing process. The method includes the steps of preparing magnesium-aluminum hydrotalcite, and the use of regenerated coarse aggregate, river sand, silicate cement and other components in the concrete, and performs high-temperature circulation treatment and secondary crushing treatment to improve the reuse performance of the aggregate.

Benefits of technology

After 100,000 fatigue load loads of recycled concrete, the compressive strength is greater than 37.9MPa and the flexural strength is greater than 4.79MPa, and the mechanical properties are better. At the same time, the crushed recycled coarse aggregate can be used in structural concrete engineering again, which improves the utilization rate and level of recycled resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a method for preparing recycled concrete with high fatigue load resistance and recycling aggregate. Comprising the following steps: step 1, weighing raw materials including magnesium chloride, aluminum chloride, sodium hydroxide and deionized water, and preparing Mg-Al hydrotalcite from the raw materials; step 2, weighing raw materials: recycled coarse aggregate, river sand, cement, fly ash, silica fume, a water reducing agent, Mg-Al hydrotalcite and water, and stirring the raw materials to obtain recycled concrete with high fatigue load resistance; 3, carrying out a fatigue load test on the concrete; and step 4, carrying out secondary crushing treatment on the concrete subjected to the fatigue load test, and after the obtained recycled coarse aggregate is pretreated, the physical properties of the recycled coarse aggregate meet the performance requirements of the III-type recycled coarse aggregate, and the recycled coarse aggregate can be used for preparing structural concrete again. The prepared concrete is good in mechanical property and good in fatigue load resistance, meanwhile, recycling of aggregate can be achieved, and economical efficiency and environment friendliness are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing recycled aggregate concrete with high fatigue load resistance and recycling aggregate. Background Art

[0002] Concrete is the most widely used building material in the world, with an annual output of nearly 20 billion tons. Large-scale concrete production has led to overconsumption and shortage of natural resources, such as natural aggregates. In addition, the demolition of buildings after their service life has ended generates a large amount of construction waste. It is reported that more than 3 billion tons of construction waste are generated worldwide each year. This construction waste is usually landfilled, which has a negative impact on the environment. In order to dispose of construction waste in an environmentally friendly way and save natural coarse aggregate resources, scholars have suggested processing and crushing construction waste into aggregates for the production of recycled aggregate concrete. As a sustainable building material, recycled aggregate concrete has unique advantages and broad application prospects.

[0003] Hydrotalcite is a layered double hydroxide, an exchangeable clay compound consisting of positively charged cation layers and interlayer anions. This compound has a wide range of applications in ion adsorption, coating protection, wastewater purification, etc. The layered structure of hydrotalcite has a certain plasticity and flexibility, which can improve the toughness of concrete through interaction with the concrete matrix. Its nano-scale size can be evenly distributed in the cement matrix, preventing the initiation and expansion of cracks, thereby improving the crack resistance of concrete.

[0004] The performance of recycled aggregate concrete is worse than that of natural concrete due to the high porosity of the mortar attached to the recycled coarse aggregate and some micro cracks generated during the crushing of construction waste. In engineering projects such as bridges and dams, concrete is often subjected to cyclic fatigue loads from automobiles or water pressure. Repeated cyclic loading can lead to structural failure even when the load is below its ultimate bearing capacity, which is critical to the service life of concrete. The results show that recycled aggregate increases the variability of concrete fatigue life while reducing its fatigue strength. When 100% recycled coarse aggregate is used, the residual strength of concrete after uniaxial compression fatigue is reduced by more than 20%. Improving the fatigue performance of RAC is crucial for its engineering applications, especially for 100% recycled coarse aggregate concrete. Summary of the invention

[0005] In order to solve the shortcomings of the prior art, the present invention provides a recycled concrete with high fatigue load resistance. The concrete has good mechanical properties and good fatigue load resistance. After the fatigue load loading cycle is 100,000 times, the recycled coarse aggregate obtained by crushing the recycled concrete can be used again in structural concrete.

[0006] Another object of the present invention is to provide a method for preparing recycled concrete with high fatigue load resistance and recycling aggregates, which is beneficial to the industrial production of concrete and its products.

[0007] In order to solve the deficiencies of the prior art, the technical solution provided by the present invention is: A recycled concrete with high fatigue load resistance comprises the following components in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water and 5-13 parts of hydrotalcite.

[0008] Wherein, the hydrotalcite is magnesium aluminum hydrotalcite or calcium aluminum hydrotalcite, preferably magnesium aluminum hydrotalcite.

[0009] The preparation method of the magnesium aluminum hydrotalcite comprises the following steps: S1: dissolving magnesium chloride and aluminum chloride in deionized water at a molar ratio of 2:1 to obtain a metal salt mixed solution; S2: preparing a sodium hydroxide solution having a concentration of 1.5 molarity by preparing sodium hydroxide powder; S3: adding sodium hydroxide solution dropwise into the stirring metal salt solution to generate a white precipitate; S4: aging the precipitate obtained by the reaction at room temperature for 24 hours; S5: centrifugally separating the generated hydrotalcite precipitate; S6: Drying the precipitate to obtain Mg-Al hydrotalcite powder.

[0010] Preferably, in step S3, the pH value of the reaction is controlled to be about 9 to 10.

[0011] Preferably, in step S5, the centrifuge is a desktop centrifuge with a rotation speed of 4000 rpm and a centrifugation time of 10 to 20 minutes.

[0012] Preferably, in step S6, the drying temperature is 50-80° C., and the hydrotalcite is dried until its weight reaches a constant value.

[0013] Among the components of the recycled concrete with high fatigue load resistance described in the present invention, Preferably, the ratio of silicate cement, fly ash and silica ash is 16:3:1.

[0014] Preferably, the coarse aggregate is natural granite with a particle size of 5 mm to 20 mm.

[0015] Preferably, the river sand is medium sand with a particle size less than 4.75 mm and a fineness modulus of 2.4 to 2.6.

[0016] Preferably, the strength grade of the silicate cement is 42.5.

[0017] Preferably, the fly ash is Class I fly ash.

[0018] Preferably, the SiO2 content in the silica ash is 94.8%.

[0019] Preferably, the water reducing agent is a polycarboxylic acid high performance water reducing agent with a water reducing efficiency of 20 to 30%.

[0020] Preferably, the magnesium chloride is a colorless crystalline solid with a purity of ≥ 98%.

[0021] Preferably, the aluminum chloride is light yellow crystals with a purity of ≥ 98%.

[0022] Preferably, the sodium hydroxide is a white powdery solid with a purity of ≥ 98%.

[0023] Preferably, the pH value of the deionized water is close to 7, and the conductivity is lower than 1 µS / cm.

[0024] The present invention also provides a method for preparing recycled concrete with high fatigue load resistance, comprising the following steps: (1) Put the coarse aggregate and river sand into a mixing container and mix them evenly; the mixing container is a single-horizontal shaft forced concrete mixer, the mixing speed is 90-140 rpm / min, and the mixing time is 25-30 s; (2) Add 45-55% water into a mixing container and stir evenly; the stirring time is 25-30 seconds; (3) Add silicate cement, fly ash, silica fume and hydrotalcite into a mixing container and mix them evenly; the mixing time is 30 to 40 seconds; (4) Add the water reducer and the remaining water into the mixing container and mix well; the stirring time is 2 to 3 minutes; (5) The mixed material is placed into molds of 100 mm × 100 mm × 100 mm and 100 mm × 100 mm × 400 mm and compacted in three layers during the pouring process; (6) Place the finished mold on a vibration table for 5 to 10 seconds, let it stand for 24 hours, then demould it. Then move it into a standard curing room with a temperature of 20 ± 2 °C and a relative humidity of 95% ± 3% for 28 days.

[0025] The present invention further provides a method for recycling recycled concrete aggregate with high fatigue load resistance, comprising the following steps: a: The concrete specimen is crushed by a crusher; b: The aggregate obtained from the primary crushing treatment is pre-processed by high-temperature circulation, and then a crusher is used for secondary crushing; the obtained recycled coarse aggregate is soaked, cleaned, dried and cooled.

[0026] Wherein, in the step a, the crusher is a jaw crusher, the movable jaw operates at a frequency of 85 to 125 times / min, the feed particle size is less than 125 mm, and the discharge particle size is 10 to 40 mm; In the step b, the high temperature cycle treatment is heating to 400-500°C, followed by cooling, and the cycle is repeated 2-3 times; In the step b, the crusher is a rolling crusher, the rotor rotation frequency is 230-260 times / min, the rotor deflection angle is 2-3°, the movable jaw working frequency is 85-125 times / min, and the discharge particle size is 0-20 mm.

[0027] Beneficial effects of the present invention: The concrete provided by the present invention has a compressive strength greater than 37.9 MPa and a flexural strength greater than 4.79 MPa after 100,000 fatigue load cycles, and has good mechanical properties; the mass loss rate after 100,000 fatigue load cycles is less than 2.0%, the relative dynamic elastic modulus is greater than 90.7%, and the durability is good.

[0028] The recycled coarse aggregate prepared by the concrete of the present invention has an apparent density greater than 2342 kg / m 3 The water absorption rate is less than 6.5%, the crushing value is less than 13.8%, and the firmness (mass loss) is less than 5.7%. Its physical properties meet the performance requirements of Class III recycled coarse aggregate and can be used again in structural concrete projects, improving the utilization level and utilization rate of recycled resources. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0030] An embodiment of the present invention provides a recycled concrete with high fatigue load resistance, comprising the following components in parts by weight: a recycled concrete with high fatigue load resistance, comprising the following components in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of silicate cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 5-13 parts of hydrotalcite.

[0031] The addition of fly ash and silica fume in the present invention can fill the internal pores of concrete and refine the internal pore structure. At the same time, the micro-aggregate filling effect and volcanic ash reaction of fly ash and silica fume will further improve the hydration reaction of concrete and enhance the mechanical properties of concrete.

[0032] In a preferred embodiment of the present invention, the recycled concrete with high fatigue load resistance includes the following components in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 8.64 parts of Mg-Al hydrotalcite.

[0033] In a preferred embodiment of the present invention, the coarse aggregate is natural granite with a particle size of 5 mm to 20 mm.

[0034] In a preferred embodiment of the present invention, the river sand is medium sand with a particle size of less than 4.75 mm and a fineness modulus of 2.4.

[0035] In a preferred embodiment of the present invention, the strength grade of Portland cement is 42.5.

[0036] In a preferred embodiment of the present invention, the fly ash is Class I fly ash.

[0037] In a preferred embodiment of the present invention, the SiO2 content in the silica ash is 94.8%.

[0038] In a preferred embodiment of the present invention, the ratio of silicate cement, fly ash and silica fume is 16:3:1.

[0039] In a preferred embodiment of the present invention, the water reducing agent is a polycarboxylic acid high performance water reducing agent, and the water reducing efficiency is 20-30%, preferably 25%.

[0040] In a preferred embodiment of the present invention, magnesium chloride is a colorless crystalline solid with a purity of ≥ 98%.

[0041] In a preferred embodiment of the present invention, aluminum chloride is light yellow crystals with a purity of ≥ 98%.

[0042] In a preferred embodiment of the present invention, sodium hydroxide is a white powdery solid with a purity of ≥ 98%.

[0043] In a preferred embodiment of the present invention, the pH value of the deionized water is close to 7 and the conductivity is lower than 1 µS / cm.

[0044] In a preferred embodiment of the present invention, the particle size of Mg-Al hydrotalcite is 10 to 80 nanometers, and the specific surface area is 10.1 m 2 / g.

[0045] A method for preparing recycled concrete with high fatigue load resistance and recycling aggregates, comprising: Step 1, preparation of Mg-Al hydrotalcite: Weigh each component according to the weight of the aforementioned recycled concrete with high fatigue load resistance; dissolve magnesium chloride and aluminum chloride in deionized water at a molar ratio of 2:1 to obtain a metal salt mixed solution; prepare a sodium hydroxide solution with a concentration of 1.5 molar concentration by sodium hydroxide powder; add the sodium hydroxide solution dropwise to the stirring metal salt solution, control the pH value of the reaction to be about 9-10, and generate a white precipitate; mature the precipitate obtained by the reaction at room temperature for 24 hours; centrifuge the generated hydrotalcite precipitate by desktop centrifuge; dry the hydrotalcite at 50-80°C to constant weight; Step 2: Prepare concrete: Weigh each component according to the weight of the aforementioned recycled concrete with high fatigue load resistance; add recycled coarse aggregate and river sand into a mixing container and stir evenly for 25 to 30 seconds; add 45% to 55% of water into a mixing container and stir evenly for 25 to 30 seconds; add silicate cement, fly ash, silica fume and the prepared Mg-Al hydrotalcite into a mixing container and stir evenly for 30 to 40 seconds; add a water reducer and the remaining water into a mixing container and stir evenly for 2 to 3 minutes; put the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds, tamp them in three layers during the pouring process, and then place the poured mold on a vibration table for compaction for 5 to 10 seconds, let it stand indoors for 24 hours and then demould it, and then move it into a standard curing room with a temperature of 20±2°C and a relative humidity of 95%±3% for curing for 28 days.

[0046] Step 3: Conduct a normal road vehicle load simulation test on the concrete: To simulate the fatigue load of ordinary vehicles on the road, four-point loading and sine wave are used, and the stress level is set to 0.5. The stress ratio is set to 0.1. In order to reflect the actual fatigue of the road panel, the number of fatigue loading cycles is set to 100,000 times. The frequency of the loading cycle is 10 Hz.

[0047] Step 4: Preparation of second generation recycled coarse aggregate: The concrete specimens subjected to 100,000 fatigue load cycles in step 2 were crushed using a jaw crusher, with a movable jaw operating frequency of 85 to 120 times / min, a feed size of less than 125 mm, and a discharge size of 10 to 40 mm; the recycled coarse aggregate obtained from the primary crushing process was heated to 400 to 500 ° C, then cooled, and cycled 2 to 3 times. A rolling crusher was used for secondary crushing, with a rotor rotation frequency of 230 to 260 times / min, a rotor deflection angle of 2 to 3°, a movable jaw operating frequency of 85 to 125 times / min, and a discharge particle size of 0 to 20 mm. The recycled coarse aggregate was soaked, cleaned, dried, and cooled. Finally, the physical properties of the recycled coarse aggregate were tested according to the specifications.

[0048] Preferably, in step 1, the centrifuge is a desktop centrifuge with a rotation speed of 4000 rpm and a centrifugation time of 10 to 20 minutes.

[0049] Preferably, in step 2, the mixing container is a single-horizontal-shaft forced concrete mixer, and the mixing speed is 90 to 140 rpm / min.

[0050] Preferably, in step three, the loading stress of the bending fatigue test is calculated as shown in

[0077] and

[0078] .

[0051]

[0052]

[0053] Among them, P max and P min are the maximum and minimum load stresses in the cyclic load test, F f is the failure load in the bending strength test, s is the stress level, and r is the stress ratio. After the cyclic fatigue loading test, the compressive strength and flexural strength of the recycled aggregate concrete were measured to evaluate the mechanical damage.

[0054] In the present invention, after the concrete prepared in the embodiment and the comparative example is subjected to 100,000 cycles of fatigue load loading, its compressive strength and flexural strength are measured according to GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and its mass loss rate and relative dynamic elastic modulus are measured according to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The recycled coarse aggregate prepared in step 3 is measured for its apparent density, water absorption, crushing value, and firmness according to GB / T25177-2010 "Recycled Coarse Aggregate for Concrete".

[0055] The apparent density, water absorption rate and crushing value of the recycled coarse aggregate used in the following examples and comparative examples are 2310 kg / m 3 , 5.9% and 21.4%, with a particle size of 0-20mm. The river sand used is medium sand, with a particle size of less than 4.75mm and a fineness modulus of 2.4. The cement is ordinary Portland cement with a strength of 42.5. The fly ash is Class I fly ash. The SiO2 content in silica ash is 94.8%. The water reducer is a polycarboxylic acid high-performance water reducer purchased from Hunan Zhongyan Building Materials Technology Co., Ltd., model ZY-HPWR-S, with a water reduction efficiency of 25%. Embodiment 1

[0056] Step 1, preparation of Mg-Al hydrotalcite: Weigh the following raw materials in parts by weight: 190 parts of magnesium chloride, 133 parts of aluminum chloride, 80 parts of sodium hydroxide, and 1929 parts of deionized water. Dissolve magnesium chloride and aluminum chloride in 676 parts of deionized water to obtain a metal salt mixed solution; mix sodium hydroxide powder with 1253 parts of deionized water to prepare a sodium hydroxide solution; add the sodium hydroxide solution dropwise to the stirring metal salt solution, control the pH value of the reaction to be about 9-10, and generate a white precipitate; mature the precipitate obtained by the reaction at room temperature for 24 hours; centrifuge the generated hydrotalcite precipitate through a desktop centrifuge; dry the hydrotalcite at 50-80°C to constant weight; and generate about 325 parts of Mg-Al hydrotalcite.

[0057] Step 2: Prepare concrete: Weigh the following raw materials in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 4.32 parts of Mg-Al hydrotalcite; add the recycled coarse aggregate and river sand into a mixer and stir evenly for 30 seconds; add 83 parts of water into a mixer and stir evenly for 30 seconds; add Portland cement, fly ash, silica fume and hydrotalcite into a mixer and stir evenly for 30 seconds; Add the water reducer and the remaining 84 parts of water into a mixer and mix evenly for 2 to 3 minutes. Load the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds and compact them in three layers during the pouring process. Then place the poured mold on a vibration table to compact it for 5 to 10 seconds. After standing indoors for 24 hours, demould it and move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0058] Step 3: Conduct a normal road vehicle load simulation test on the concrete: To simulate the fatigue load of ordinary vehicles on the road, four-point loading and sine wave were used, and the stress level was set to 0.5. The stress ratio was set to 0.1. In order to reflect the actual fatigue of the road panel, the number of fatigue loading cycles was set to 100,000 times. The frequency of the loading cycle was 10 Hz.

[0059] Step 4: Preparation of second generation recycled coarse aggregate: The concrete specimens subjected to 100,000 fatigue load cycles in step 2 were crushed using a jaw crusher, with a movable jaw operating frequency of 85 to 120 times / min, a feed size of less than 125 mm, and a discharge size of 10 to 40 mm; the recycled coarse aggregate obtained from the primary crushing process was heated to 400 to 500 ° C, then cooled, and cycled 2 to 3 times. A rolling crusher was used for secondary crushing, with a rotor rotation frequency of 230 to 260 times / min, a rotor deflection angle of 2 to 3°, a movable jaw operating frequency of 85 to 125 times / min, and a discharge particle size of 0 to 20 mm. The recycled coarse aggregate was soaked, cleaned, dried, and cooled. Finally, the physical properties of the recycled coarse aggregate were tested according to the specifications. Embodiment 2

[0060] Step 1, preparation of Mg-Al hydrotalcite: same as Example 1.

[0061] Step 2: Prepare concrete: Weigh the following raw materials in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 8.64 parts of Mg-Al hydrotalcite; add the recycled coarse aggregate and river sand into a mixer and stir evenly for 30 seconds; add 83 parts of water into a mixer and stir evenly for 30 seconds; add Portland cement, fly ash, silica fume and hydrotalcite into a mixer and stir evenly for 30 seconds; Add the water reducer and the remaining 84 parts of water into a mixer and mix evenly for 2 to 3 minutes. Load the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds and compact them in three layers during the pouring process. Then place the poured mold on a vibration table to compact it for 5 to 10 seconds. After standing indoors for 24 hours, demould it and move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0062] Step three, conducting a normal road vehicle load simulation test on the concrete: the same as in Example 1.

[0063] Step 4: preparing second generation recycled coarse aggregate: same as in Example 1. Embodiment 3

[0064] Step 1, preparation of Mg-Al hydrotalcite: same as Example 1.

[0065] Step 2: Prepare concrete: Weigh the following raw materials in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 12.96 parts of Mg-Al hydrotalcite; add the recycled coarse aggregate and river sand into a mixer and stir evenly for 30 seconds; add 83 parts of water into a mixer and stir evenly for 30 seconds; add Portland cement, fly ash, silica fume and hydrotalcite into a mixer and stir evenly for 30 seconds; Add the water reducer and the remaining 84 parts of water into a mixer and mix evenly for 2 to 3 minutes. Load the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds and compact them in three layers during the pouring process. Then place the poured mold on a vibration table to compact it for 5 to 10 seconds. After standing indoors for 24 hours, demould it and move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0066] Step three, conducting a normal road vehicle load simulation test on the concrete: the same as in Example 1.

[0067] Step 4: preparing second generation recycled coarse aggregate: same as in Example 1. Embodiment 4

[0068] Step 1, preparation of Ca-Al hydrotalcite: Weigh the following raw materials in parts by weight: 29 parts of calcium chloride, 11 parts of aluminum chloride, 15 parts of sodium hydroxide, and 51 parts of deionized water. Dissolve magnesium chloride and aluminum chloride in deionized water at a molar ratio of 2:1 to obtain a mixed solution of metal salts; prepare a sodium hydroxide solution with a concentration of 1.5 molarity using sodium hydroxide powder; add the sodium hydroxide solution dropwise to the stirring metal salt solution, control the pH value of the reaction to be around 9-10, and generate a white precipitate; mature the precipitate obtained by the reaction at room temperature for 24 hours; centrifuge the generated hydrotalcite precipitate using a desktop centrifuge; dry the hydrotalcite at 50-80°C to constant weight; Step 2: Prepare concrete: Weigh the following raw materials in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, 169 parts of water, and 8.64 parts of Ca-Al hydrotalcite; add the recycled coarse aggregate and river sand into a mixer and stir evenly for 30 seconds; add 83 parts of water into a mixer and stir evenly for 30 seconds; add Portland cement, fly ash, silica fume and hydrotalcite into a mixer and stir evenly for 30 seconds; Add the water reducer and the remaining 84 parts of water into a mixer and mix evenly for 2 to 3 minutes. Load the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds and compact them in three layers during the pouring process. Then place the poured mold on a vibration table to compact it for 5 to 10 seconds. After standing indoors for 24 hours, demould it and move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0069] Step three, conducting a normal road vehicle load simulation test on the concrete: the same as in Example 1.

[0070] Step 4: preparing second generation recycled coarse aggregate: same as in Example 1.

[0071] Comparative Example 1 Step 1: Prepare concrete: Weigh the following raw materials by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of Portland cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducer, and 169 parts of water. ; Add recycled coarse aggregate and river sand to the mixer and stir evenly for 30 seconds; Add 83 parts of water to the mixer and stir evenly for 30 seconds; Add Portland cement, fly ash, and silica fume to the mixer and stir evenly for 30 seconds; Add water reducer and the remaining 84 parts of water to the mixer and stir evenly for 2 to 3 minutes; Put the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds, and compact them in three layers during the pouring process. Then place the poured mold on a vibrating table for compaction for 5 to 10 seconds, let it stand indoors for 24 hours, then demould it, and then move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0072] Step 2: Conducting a normal road vehicle load simulation test on the concrete: Same as in Example 1.

[0073] Step three, preparing the second generation recycled coarse aggregate: same as in Example 1.

[0074] Comparative Example 2 Step 1: Prepare concrete: Weigh the following raw materials by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 431 parts of Portland cement, 2.16 parts of water reducer, and 169 parts of water. ; Add recycled coarse aggregate and river sand to the mixer and stir evenly for 30 seconds; Add 83 parts of water to the mixer and stir evenly for 30 seconds; Add Portland cement to the mixer and stir evenly for 30 seconds; Add water reducer and the remaining 84 parts of water to the mixer and stir evenly for 2 to 3 minutes; Put the mixture into 100mm×100mm×100mm and 100mm×100mm×400mm molds, and compact them in three layers during the pouring process. Then place the poured mold on a vibrating table for compaction for 5 to 10 seconds, let it stand indoors for 24 hours, then demould it, and then move it into a standard curing room with a temperature of 20±2℃ and a relative humidity of 95%±3% for curing for 28 days.

[0075] Step 2: Conducting a normal road vehicle load simulation test on the concrete: Same as in Example 1.

[0076] Step three, preparing the second generation recycled coarse aggregate: same as in Example 1.

[0077] Table 1 Mechanical properties of concrete in the examples Table 2 Performance of the second generation recycled coarse aggregate in the examples Group <![CDATA[Apparent density (kg / m 3 )]]> Water absorption (%) Crushing value (%) Firmness (%) Embodiment 1 2318 7.1 15.3 6.1 Embodiment 2 2346 6.6 13.8 5.6 Embodiment 3 2324 6.9 14.9 6.8 Embodiment 4 2310 7.0 15.7 7.0 Comparative Example 1 2298 7.3 16.8 7.1 Comparative Example 2 2231 8.1 17.3 7.3 It can be seen from the test results in Table 1 that the recycled concrete with high fatigue load resistance prepared by the present invention, when fly ash, silica fume and hydrotalcite with four different mass replacement rates are added, has a compressive strength greater than 37.9 MPa and a flexural strength greater than 4.79 MPa after 100,000 fatigue load cycles, and has good mechanical properties; its mass loss rate is less than 2.0%, and its relative dynamic elastic modulus is greater than 90.7%, and its durability is good. In Comparative Example 1, no hydrotalcite was added to the concrete, and the same fatigue load loading cycle conditions as those in the embodiment were adopted. After 100,000 fatigue load loading cycles, its compressive strength was only 35.2 MPa, and its flexural strength was 4.75 MPa, and its mechanical properties were poor; its mass loss rate was 2.2%, and its relative dynamic elastic modulus was 89.1%, and its durability was poor; in Comparative Example 2, no fly ash, silica fume and hydrotalcite were added to the concrete, and the same fatigue load loading cycle conditions as those in the embodiment were adopted. After 100,000 fatigue load loading cycles, its compressive strength was only 35.1 MPa, and its flexural strength was 4.45 MPa, and its mechanical properties were poor; its mass loss rate was 2.1%, and its relative dynamic elastic modulus was 88.2%, and its durability was poor.

[0078] In summary, it is shown that the recycled concrete with high fatigue load resistance prepared by the present invention has good performance.

[0079] From the test results of the performance of recycled coarse aggregate in Examples 1 to 3 in Table 2, it can be seen that the recycled coarse aggregate obtained by crushing the recycled concrete with high fatigue load resistance prepared by the present invention after 100,000 cycles of fatigue load loading meets the performance requirements of Class III recycled coarse aggregate in GB / T25177-2010 "Recycled Coarse Aggregate for Concrete" and can be used again for structural concrete. In Comparative Examples 1 and 2, since the concrete is not mixed with hydrotalcite, fly ash and silica fume, the mechanical properties and durability of the concrete are poor (see Table 1), so the performance of the recycled coarse aggregate obtained by crushing after 100,000 cycles of fatigue load loading is inferior to that of the recycled coarse aggregate in Examples 1 to 3.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A recycled concrete with high fatigue load resistance, characterized in that: The invention comprises the following components in parts by weight: 921 parts of recycled coarse aggregate, 664 parts of river sand, 345 parts of silicate cement, 65 parts of fly ash, 22 parts of silica fume, 2.16 parts of water reducing agent, 169 parts of water and 5-13 parts of hydrotalcite.

2. The recycled concrete with high fatigue load resistance according to claim 1, characterized in that: The ratio of silicate cement, fly ash and silica ash is 16:3:

1.

3. The recycled concrete with high fatigue load resistance according to claim 1, characterized in that: The hydrotalcite is magnesium aluminum hydrotalcite or calcium aluminum hydrotalcite, preferably magnesium aluminum hydrotalcite.

4. The recycled concrete with high fatigue load resistance according to claim 3, characterized in that: The particle size of the magnesium aluminum hydrotalcite is 10 to 80 nanometers, and the specific surface area is 10.1 m 2 / g.

5. The recycled concrete with high fatigue load resistance according to claim 4, characterized in that: The preparation method of the magnesium aluminum hydrotalcite comprises the following steps: S1: dissolving magnesium chloride and aluminum chloride in deionized water at a molar ratio of 2:1 to obtain a metal salt mixed solution; S2: preparing a sodium hydroxide solution having a concentration of 1.5 molarity by preparing sodium hydroxide powder; S3: adding sodium hydroxide solution dropwise into the stirring metal salt solution to generate a white precipitate; S4: aging the precipitate obtained by the reaction at room temperature for 24 hours; S5: centrifugally separating the generated hydrotalcite precipitate; S6: Drying the precipitate to obtain magnesium aluminum hydrotalcite powder.

6. The method for preparing recycled concrete with high fatigue load resistance according to any one of claims 1 to 5, characterized in that: The steps include: (1) Put the recycled coarse aggregate and river sand into a mixing container and mix them evenly; the mixing container is a single-horizontal shaft forced concrete mixer, the mixing speed is 90-140 rpm / min, and the mixing time is 25-30 s; (2) Add 45-55% water into the mixing container and stir evenly; the stirring time is 25-30 seconds; (3) Add silicate cement, fly ash, silica fume and hydrotalcite into a mixing container and mix them evenly; the mixing time is 30 to 40 seconds; (4) Add the water reducer and the remaining water into the mixing container and mix well; the stirring time is 2 to 3 minutes; (5) Place the mixed material into the mold and pour and compact it; (6) Place the finished mold on a vibration table for 5 to 10 seconds, let it stand for 24 hours, then demould it and move it to a standard curing room for curing.

7. A method for recycling recycled concrete aggregate with high fatigue load resistance, characterized in that: The steps include: a: The recycled concrete with high fatigue load resistance according to any one of claims 1 to 4 is subjected to primary crushing treatment by a crusher; b: The aggregate obtained from the primary crushing treatment is pre-processed by high-temperature circulation, and then a crusher is used for secondary crushing; the obtained recycled coarse aggregate is soaked, cleaned, dried and cooled.

8. The method for recycling recycled concrete aggregate with high fatigue load resistance according to claim 7, characterized in that: In the step b, the high temperature cycle treatment is heating to 400-500° C., followed by cooling, and the cycle is repeated 2-3 times.